Numerical Analysis of Slope Stability under Reservoir Water Level Fluctuations Using a FEM-LEM-Combined Method - Qingxiang Meng; Kun Qian; Lin Zhong; Jinjian Gu; Yue Li; Kaifeng Fan; Long Yan (Geofluids)
Large-scale slopes at the banks of reservoirs pose a serious threat to the safety of hydropower stations. The fluctuation of the reservoir water level is a key factor in the slope stability. However, the parameters to describe the relationship among water content, matric suction, and soil strength are difficult to measure using unsaturated soil strength theory. To solve this problem, a simple FEM-LEM-combined scheme considering pore pressure, seepage force, and strength weakening is presented to calculate the safety factor. A numerical study on the impact of reservoir water level fluctuations on stability of a glaciofluvial deposit slope is implemented. Two typical profiles are used to estimate the stability of the glaciofluvial deposit slope in response to rising and lowering water levels. The results indicate that this method proposed a simple and efficient tool for water level-induced slope stability analysis.